Reconfigurations of illness and masculinity on Instagram - Birk Jensen, Mie; Hvidtfeldt, Karen (MedieKultur: Journal of media and communication research, 2023)
In this paper, we explore how men’s experiences of living with illness are mediatized on Instagram, thus understanding social media platforms as “sociotechnical affordances” that support and modulate how everyday lives are lived (Paasonen, 2018). The article zooms in on four Danish Instagram profiles (with approximately 2,000 followers each) that centre on experiences of living with different diagnoses, including morbus chrohn, hip dysplasia, chronic pain, and mental illness. By applying the concepts “biological entrepreneurship” (Stage, 2017), “bodywork”, and “spornosexuality” (Hakim, 2019), we examine how masculinity becomes reconfigured as a resource, rather than an opposition to health. The content on Instagram emerges as entrepreneurial by extending the body: Situated within the larger framework of the profiles’ content and their place in the platform economy of attention, illness is transformed into a narrative and an affective source, whether on the politics of gender, visibility of illness, monetary gain, or self-help.